2020
DOI: 10.5194/ms-11-371-2020
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial microstructures and properties of hyper-eutectic Al–21Si / hypo-eutectic Al–7.5Si bimetallic material fabricated by liquid–liquid casting route

Abstract: Abstract. The bimetal casting process using the liquid–liquid technique was developed to produce a high-quality hyper-eutectic Al–21Si / hypo-eutectic Al–7.5Si alloy bimetal material. Microstructure and microhardness were investigated as a function of the time interval between pouring hypo-eutectic and hyper-eutectic alloys. A bimetal material was successfully fabricated using a liquid–liquid casting technique with a 10 s time interval in a permanent mould casting. A unique structure comprised of hyper-eutecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Mohamed Ramadan et al [99] recently explored bimetal casting using the liquid-liquid method to create a bimetal of two hyper-and hypo-eutectic aluminum alloys: Al-21 wt% Si and Al-7.5 wt% Si, respectively. The results indicated that a bimetal material was effectively produced in a permanent mold casting utilizing a liquid-liquid casting process with a time interval of 10 s. A novel structure was created with a bimetal and a eutectic interface with a thickness of 70 µm.…”
Section: Sequential Casting Methods (The Liquid-liquid Casting Method)mentioning
confidence: 99%
“…Mohamed Ramadan et al [99] recently explored bimetal casting using the liquid-liquid method to create a bimetal of two hyper-and hypo-eutectic aluminum alloys: Al-21 wt% Si and Al-7.5 wt% Si, respectively. The results indicated that a bimetal material was effectively produced in a permanent mold casting utilizing a liquid-liquid casting process with a time interval of 10 s. A novel structure was created with a bimetal and a eutectic interface with a thickness of 70 µm.…”
Section: Sequential Casting Methods (The Liquid-liquid Casting Method)mentioning
confidence: 99%
“…The experimental time interval of 10 s is less than that obtained by theoretical TST, with about 2 s for the same cast modulus. Previous work [24] reported an optimum experimental time interval of 10 s for Al-21Si/Al-7.5Si bimetal composite in a metallic mould. The optimum time interval of Al/Al bimetal casting in metallic moulding was estimated by subtracting 1-5 s from the TST value of M1, considering theoretical and experiment errors.…”
Section: Time Interval Estimation For Al/al Bimetal Casting In Sand A...mentioning
confidence: 99%
“…On the other hand, liquid-liquid methods have seen very little research published due to the requirement for two melting furnaces and two gating systems. In addition, it is essential to cautiously control the time between pouring the first metal and the second metal [24].…”
Section: Introductionmentioning
confidence: 99%
“…Liquid–liquid compound casting is a method of direct-compounding two liquid alloys through a certain casting process without coating treatment. This technique offers an effective means to simplify the preparation process of bimetallic composites without introducing heterogeneous elements [ 11 , 12 ]. Because of the good fluidity of a liquid aluminium alloy, an oxide layer can be very easily formed on its surface.…”
Section: Introductionmentioning
confidence: 99%